2022
DOI: 10.1111/apt.16816
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to accept risk with medication in return for cure of symptoms among patients with Rome IV irritable bowel syndrome

Abstract: Background: Some drugs for irritable bowel syndrome (IBS) have serious side effects. Aims:To examine the willingness of individuals with IBS to accept risks with medication in return for symptom cure. Methods:We collected demographic, gastrointestinal symptoms, psychological health, quality of life and impact on work and daily activities data from 752 adults with Rome IV-defined IBS. We examined median willingness to accept death in return for cure with a hypothetical medication using a standard gamble, accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…Goodoory and colleagues explore the issue of risk in irritable bowel syndrome (IBS), a common disorder that can significantly impair quality of life 1 . Its non‐fatal nature has engendered an attitude of zero tolerance for serious adverse events among regulators and resulted in the withdrawal of drugs such as alosetron 2 and tegaserod 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Goodoory and colleagues explore the issue of risk in irritable bowel syndrome (IBS), a common disorder that can significantly impair quality of life 1 . Its non‐fatal nature has engendered an attitude of zero tolerance for serious adverse events among regulators and resulted in the withdrawal of drugs such as alosetron 2 and tegaserod 3 .…”
mentioning
confidence: 99%
“…In adopting an approach previously employed elsewhere, such as natalizumab in multiple sclerosis, 5–7 to gauge the willingness of sufferers to tolerate risk in return for cure, Goodoory found that IBS sufferers were prepared to accept a median 2% risk of death from a medication in return for a 98% chance of permanent cure 1 . A prior study found that IBS sufferers were prepared to relinquish 15 years of life to achieve perfect health 8…”
mentioning
confidence: 99%
“…We thank Dr Quigley for his interest in our article, 1 and raising important discussion points. 2 Although we agree, and have previously demonstrated, that the Rome IV criteria for irritable bowel syndrome (IBS) select a population of individuals with more severe disease, 3,4 we believe that our study population was a representative sample of individuals with IBS according to these criteria.…”
Section: N V I T E D E D I T O R I a L Editorial: Risky Business What...mentioning
confidence: 95%
“…The authors' declarations of personal and financial interests are unchanged from those in the original article 1 …”
Section: Acknowledgementmentioning
confidence: 99%
“…3 It also creates the false impression that IBS is not burdensome. However, in another recent article from our group, people with IBS were willing to accept a median 2% risk of death in return for a 98% chance of permanent cure of their condition, 4 demonstrating the substantial impact of symptoms on individuals who experience them.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 96%